Intervensi media video berpengaruh pada pengetahuan dan sikap remaja putri dalam mencegah kurang energi kronik - Waryana, Waryana; Sitasari, Almira; Febritasanti, Danissa Wulan (AcTion: Aceh Nutrition Journal, 2019)
Community-based interventions to overcome chronic energy malnutrition among women of childbearing age and pregnant women can be done with communication, education, and information. Video can be useful for education purpose. The goal of this study was to determine whether video may have different effect to knowledge and attitude on preventing energy malnutrition among teenage girls compared to food model intervention. The Research a quasi experiment with pre-post test with control group design was conducted in Tridadi Village, Sleman in May 2018. Teenage girls in intervention group were asked to view video specifically developed for the study. Knowledge and attitude on energy malnutrition was assessed right after the intervention. Data were analyzed using paired and independent t-test. The results a total of 54 teenage girls completed the study. The pretest average score on knowledge was 7,09 in the control group, and 7,70 in the intervention group. The pretest average score of attitudes was 24,11 in the control group and 25,00 in the intervention group. While the post test average score on knowledge was 7,37 in the control group and 8,44 in the intervention group. The average post test score of attitude was 26,70 in the control group and 28,38 in the treatment group. The results showed that video intervention has different effect on knowledge (p= 0,00) and attitude (p= 0,01) on chronic energy malnutrition prevention compared to education with food model. Conclusion, there are difference knowledge and attitude between video intervention group and food model education group on chronic energy malnutrition prevention among teenage girls. Intervensi melalui pendekatan komunitas untuk penanggulangan kekurangan energi kronis (KEK) pada wanita usia subur dan ibu hamil dapat dilakukan melalui komunikasi, informasi, dan edukasi. Intervensi video dapat menjadi alternatif pemecahan masalah tersebut khususnya untuk meningkatkan pengetahuan dan sikap pencegahan KEK pada remaja putri. Penelitian bertujuan untuk mengetahui  perbedaan  pengetahuan dan sikap remaja putri  dalam pencegahan kurang energi kronik (KEK)  antara yang diintervensi penyuluhan dengan media  video dan dengan   food model. Penelitian ini adalah eksperimen semu dengan menggunakan rancangan pre-post test with control group design. Penelitian dilaksanakan pada bulan Mei 2018. Remaja putri pada kelompok intervensi diberikan perlakuan menonton video yang sebelumnya telah dikembangkan untuk studi ini. Pengetahuan dan sikap dinilai setelah proses menonton video Analisis data menggunakan independent sample t- test. Hasil penelitian menunjukkan adanya pengaruh pemberian media video terhadap perubahan pengetahuan (p= 0,00) namun tidak pada sikap pencegahan kurang energi kronis (p= 0,01). Kesimpulan, terdapat perbedaan pengetahuan dan sikap remaja putri antara grup media  video dan grup media food model dalam edukasi tentang pencegahan kurang energi kronik pada remaja putri.